Stereoselective synthesis of E-monofluorovinyl pyridin-4-yl ethers by the reaction of gem-difluoroalkenes with pyridin-4-yl boronic acid and oxygen. (24th March 2023) - Zhang, Xuxue; Sun, Yuzhen; Yan, Xinsheng; Jin, Chen; Deng, Yupian; Cao, Song
Graphical abstract: Highlights: Monofluorovinyl esters are important structural motifs. The functionalized monofluoroalkenes are valuable synthetic intermediates. gem-Difluoroalkenes reacted with pyridin-4-yl boronic acid and oxygen. Stereoselective synthesis of E-monofluorovinyl pyridin-4-yl ethers. Abstract: A convenient and efficient method for the highly stereoselective synthesis of E -monofluorovinyl pyridin-4-yl ethers by the reaction of gem -difluoroalkenes with pyridin-4-yl boronic acid and oxygen with the assistance of K3 PO4 is described.